Use of Masquelet technique in treatment of septic and atrophic fracture nonunion - Raven, Tim Friedrich; Moghaddam-Alvandi, Arash; Ermisch, Claudia; Westhauser, Fabian; Heller, Raban; Bruckner, Thomas; Schmidmaier, Gerhard (Injury, 2019)
Background - Treatment of atrophic non-unions and large bone defects or infections remains a challenging task for the treating surgeon. In the herein study, we present our experience of the 'Masquelet technique' according to the 'diamond concept' for the treatment of complex long bone reconstruction procedures. - Methods - Between February 2010 and March 2015, 150 patients (mean age 51.4) with atrophic and- /or infected non-unions were included in this prospective study. All patients received autologous bone graft, a graft expander (TCP (tricalcium phosphate)) and BMP (bone morphogenic protein). Clinical and radiological parameters were assessed at 6 weeks, and at 3, 6 and 12 months. The SF-12 questionnaire was used to evaluate the subjective health of patients. - Results - A successful bony consolidation of the non-unions was observed in 120 (80%) cases with a median healing time of 12.1 months. The mean defect gap was 4.4cm. Initial infection was documented in 54 cases. The most frequently identified pathogen was staphylococcus epidermidis and staphylococcus aureus. A successful removal of microorganisms with subsequent healing was achieved in 39 cases (72%). The SF-12 scores of subjective physical and mental health increased from PCS 31.5 preoperatively to 36.7 one year postoperatively, while MCS increased from 45.5 to 48.7. - Conclusions - Our study showed that the Masquelet technique according to the 'diamond concept' is a valid method to treat complex atrophic non-unions with large bone defects and associated infection. Following the principles of the 'diamond concept' (targeted optimization of tissue engineering and bone regeneration) a high rate of success can be expected in these difficult reconstruction cases.
Gesehen am 02.01.2019